Analisis Perbandingan Metode Moving Average dan Exponential Smoothing untuk Meramalkan Permintaan Produk Turning Pada CV. Gavra Perkasa - Suparno Suparno; Anik Rufaidah (Jurnal Optimalisasi, 2021)
CV. Gavra Perkasa is a manufacturing industry with the finished product in the form of turning. The number of sales transactions will affect the inventory of raw materials. The problem with the company is that the company's ability to predict the amount of raw materials that must be available in the following month is not optimal due to fluctuating demand. This problem will have an impact on planning inventory inventory during the production process and recording inventory usage to optimize storage costs. This study aims to plan inventory demand in the future and to plan inventory use using the Moving average  and Exponential smoothing methods. These two methods are used because the results of the demand data plot show a stationary data pattern. The accuracy of the forecasting results was analyzed with the smallest MSE, MAD, and MAPE results. Based on the analysis results, the 5-month MA method is the most accurate with prediction results in 2017 of 57000 units with MAD, MSE, and MAPE values of 3684.21, 24345260, and 0.07.